PENGARUH GIMKIT TERHADAP MOTIVASI BELAJAR SISWA KELAS V PADA MATERI PERUBAHAN BUMI - Aina Mutmainnah; Panjaitan, Regina Lichteria; Sujana, Atep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of Gimkit interactive media on the learning motivation of fifth grade students in the IPAS subject of Earth Changes material. The background of this study is the low motivation of students to learn in conventional learning. The method used was quasi-experiment with Nonequivalent Control Group Design. The sample consisted of two classes, 30 students each, namely the experimental class using Gimkit and the control class using conventional methods. Data were collected through questionnaires and observations. The results showed that the implementation of learning using Gimkit was very well implemented with an average implementation of 96%. The average experimental class student learning motivation questionnaire score increased from 41.97 to 44.43. Wilcoxon and Paired T-Test tests showed significant differences before and after treatment. The Mann-Whitney U test also showed a significant difference between the two classes after treatment (Sig. = 0.003). The N-Gain test results showed an increase in motivation in the low category, namely 0.246 for the experimental class and 0.169 for the control class. However, the effect size calculation of 0.396 indicates a moderate influence. Thus, Gimkit interactive media has a positive effect on student learning motivation, although the increase is still limited by technical constraints and student adaptation to media use.